Representation, voice and producer–consumer communication in fair trade movements: Toward new empirical directions. Issue 117 (December 2020) - Touri, Maria
Highlights: Fair trade's marketing is based on objectifying representation of farmers. Consumers need authentic representations of farmers and food production processes. Fair trade farmers have the knowledge to create pedagogical marketing stories. Farmer participation in fair trade marketing empowers them. Farmers' self- representations can challenge consumers' colonial perceptions. Abstract: Representation is integral in the remit of the fair trade movement for social justice, but fair trade's communication is built on stereotypical portrayals that objectify Southern producers. Although such portrayals have received ample scholarly critique for upholding neo-colonial relations by reinforcing western consumers' colonial fantasies, there is still a dearth of research into if and how a more truthful and dynamic representation can be built. The article moves the debate forward with a novel experiment that explores new possibilities for producer–consumer connections by 'connecting' an Indian farming community with a group of consumers in the UK through short videos and stories created by the farmers. The findings highlight the need to re-think the role of representation in fair trade since when farmers construct their representations on their own terms, they engage in reflexive and dialogic processes that prove empowering. Moreover, including the farmers' voices in these representations has the capacity to challenge consumers' colonial perceptions about the distant other. The experiment also sheds light on the challenges that are inherent in reframing fair trade's discourses and creating more inclusive and interactive communication strategies.